Opioid-Induced Foregut Dysfunction. (November 2019) - Patel, Dhyanesh; Callaway, James; Vaezi, Michael
Abstract : The impact of opioid use on the lower gastrointestinal tract is well described, but recent opioid crisis has caused increased awareness of the detrimental effects of these drugs on esophageal and gastroduodenal motility. Opioid use has been associated with increased incidence of spastic esophageal motility disorders and gastroduodenal dysfunction. Opioid receptors are present with high abundance in the myenteric and submucosal plexus of the enteric nervous system. Activation of these receptors leads to suppressed excitability of the inhibitory musculomotor neurons and unchecked tonic contraction of the autogenic musculature (such as the lower esophageal sphincter and the pylorus).